2012
DOI: 10.1007/s00296-012-2565-3
|View full text |Cite
|
Sign up to set email alerts
|

A primary analysis of sexual problems in Chinese patients with ankylosing spondylitis

Abstract: While the physical impact of ankylosing spondylitis (AS) is central to clinical treatment, the sexual problems associated with AS are often overlooked. Sexual problems may be related to a variety of undocumented demographic parameters, physical impairments, and psychological problems. These associations were examined through a single-center cross-sectional study of 103 AS patients (78 males and 25 females) and 121 healthy individuals (73 males and 48 females). All participants provided information pertaining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
5
17
0
Order By: Relevance
“…Using IIEF, our study demonstrates that sexual problems are significantly more prevalent in male AS patients as compared to normal subjects. This is similar to other studies which have reported significant deterioration of sexual function in AS males. A few have reported sexual problems in female AS patients as well …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Using IIEF, our study demonstrates that sexual problems are significantly more prevalent in male AS patients as compared to normal subjects. This is similar to other studies which have reported significant deterioration of sexual function in AS males. A few have reported sexual problems in female AS patients as well …”
Section: Discussionsupporting
confidence: 92%
“…Impairment of partner relationships and social life in AS patients has been shown by Shen et al . and Ozgül et al ., respectively.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…[18,22] Besides Shen et al shown the association between disturbed social function impeded by depression and sexual dysfunction. [23] Quality of life is impeded by both chronic diseases and sexual dysfunctions. The diminishment of quality of life (QoL) in patients with AS, a chronic inflammatory disease has already been established in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Another study compared AS male patients' ED with healthy controls and found a significantly higher frequency of ED in AS patients [6]. Shen et al [7] conducted a study on the sexual problems of 103 AS patients in China. They found that the rate of the prevalence and severity of sexual dysfunction in AS patients was much higher than that observed in healthy individuals.…”
Section: Introductionmentioning
confidence: 97%